THE LIVING QUR’AN IN THE BARZANJI TRADITION: INTEGRATING THE SACRED TEXT AND LOCAL CULTURE - Fahmi Al-Mahfudh; Abdurrahman Mas’ud; M. Khikamuddin (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2025)
This study departs from the central question: how is the form of the Living Qur’an manifested in the Barzanji tradition in Gunungtelu Village, Karangpucung District, Cilacap Regency, and what are its impacts on worship practices and the community’s religious life? The purpose of this research is to analyze the expression of the Living Qur’an through the Barzanji tradition and to examine its influence on the religious practices of the local community. The research employs a qualitative field method with a phenomenological approach, in which data were collected through participatory observation, in-depth interviews, and documentation. Data analysis was carried out descriptively, analytically, and interpretatively, using Ahmad Rafiq’s Living Qur’an theoretical framework. The findings reveal that the recitation of Barzanji in Gunungtelu is based on QS. al-Ahzab [33]: 56 and is routinely practiced twice a week. This tradition not only strengthens religious practices such as congregational prayer, dhikr, and religious study but also cultivates love for the Prophet Muhammad (peace be upon him), reinforces social solidarity, and serves as a medium for integrating religious values with Nahdlatul Ulama culture. Thus, the Living Qur’an in the practice of Barzanji is present not merely as a text to be recited but as a socio-cultural practice that shapes religious habitus and preserves local Islamic heritage.